The effect of music education on the social values of preschool children - CAN, AJDA AYLİN (My University, 2020)
This study aims to explore the effect of music education on the acquisition of social values by preschool children. In this study, a quasi-experimental pattern model with the pretest–posttest control group is employed. The Preschool Social Values Scale is used for collecting the data. The participants of this study are 26 preschool children (the experimental and control groups contain 13 children each). Whilst the experimental group underwent 30 minutes of music training twice a week for 10 weeks, the control group pursued their preschool education. Music education with the experimental group consists of activities, where students are active and experience music. Songs containing social values were taught to children in the unity of play music and movement. At the end of the study, the scores related to the social values of the experimental group improved as compared to that of the control group. No meaningful difference was detected between the posttest and follow-up test social values’ scores.          Keywords: Music education, social values, preschool education, value education.